2023
DOI: 10.3390/rs15092481
|View full text |Cite
|
Sign up to set email alerts
|

Six Years of IKFS-2 Global Ozone Total Column Measurements

Abstract: Atmospheric ozone plays an important role in the biosphere’s absorbing of dangerous solar UV radiation and its contributions to the Earth’s climate. Nowadays, ozone variations are widely monitored by different local and remote sensing methods. Satellite methods can provide data on the global distribution of ozone and its anomalies. In contrast to measurement techniques based on solar radiation measurements, Fourier-transform infrared (FTIR) satellite measurements of thermal radiation provide information, regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Observations, as well as the results of numerical experiments, show that the stratospheric polar vortex is warmer and more disturbed under conditions of a positive ENSO phase [20]; the situation is the opposite during a cold phase [25]. The activity of stationary planetary waves with the zonal wave number 1 (SPW1) is higher in the stratosphere and weaker at middle latitudes at the stratospheric jet maximum region during El Niño's mid-winter.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Observations, as well as the results of numerical experiments, show that the stratospheric polar vortex is warmer and more disturbed under conditions of a positive ENSO phase [20]; the situation is the opposite during a cold phase [25]. The activity of stationary planetary waves with the zonal wave number 1 (SPW1) is higher in the stratosphere and weaker at middle latitudes at the stratospheric jet maximum region during El Niño's mid-winter.…”
Section: Introductionmentioning
confidence: 98%
“…From the point of view of remote sensing, the polar stratosphere is a complex object of study. Polyakov et al [20] showed that low signal and small vertical temperature gradients significantly increase the errors in satellite ozone determinations. To increase the accuracy of satellite sensing, the highest quality a priori information is used-modeling and reanalysis data.…”
Section: Introductionmentioning
confidence: 99%
“…The IKFS-2 FTIR spectrometer operating onboard the Meteor-M 2 satellite is described in [ 21 ]; it allows measurements of the gas composition of the atmosphere with a maximum bandwidth of up to 2500 km (with a point step of 100 km). The IKFS-2 FTIR spectrometer’s instantaneous field of view (IFOV) is 40 mrad (35 km), its spectral range is 660–2000 cm and its mass is about 50 kg [ 22 ]. The GaoFen-5 satellite-II (GMI-II) uses spatial heterodyne spectroscopy (SHS) for quantitative monitoring of atmospheric greenhouse gases [ 23 ].…”
Section: Introductionmentioning
confidence: 99%